Unsur–Unsur Iklim yang Berhubungan dengan Incidence Rate Demam Berdarah Dengue di Kabupaten Malang Tahun 2011-2020 - Muhamad Jihad Fernanda Putra; Kusuma Scorpia Lestari (Media Gizi Kesmas, 2023)
Background: As a tropical country, Indonesia is one of the highest contributors to dengue cases. In the last four years, Malang Regency has increased in rank as the region with the highest dengue cases in East Java East Java Province. The increase in DHF cases will be followed by an increase in the Incidence Rate. Global warming causes fluctuations in the climatic factor. The increase and decrease in climatic elements can affect mosquito's life cycle as vectors of the dengue virus carriers Objectives: This study aims to analyze the relationship between climate elements in the form of rainfall, air temperature, humidity, and wind speed with the incidence rate of monthly dengue cases in Malang Regency in 2011 – 2020. Methods: This study was a quantitative study with an ecological study design using secondary data. The sample in this study used total sampling and analyzed univariately to describe the frequency distribution and bivariate analysis using Spearman's correlation to identify the degree of closeness of the relationship. Results: The results of this study indicated that there was a relationship between the incidence rate of dengue fever and climate elements in the form of rainfall (p = 0.005), air temperature (p = 0.003), humidity (p = 0.000) and wind speed (p = 0.000). Conclusions: The climatic factors related to cases of Dengue Hemorrhagic Fever are rainfall, air temperature, humidity, and wind speed.